Simulation Study on Freeze-drying Characteristics of Mashed Beef - Armansyah H. Tambunan; M. Solahudin; Estri Rahajeng (PERTETA, 2000)
Drying characteristic of a particular product is important in analyzing the appropriateness of the drying method for the product. This is especially important for freeze drying, which is known as the most expensive drying method, asideji-om its good drying quality. The objectives of this experiment are to develop a computer simulation program using a retreating drying-frontmodel for predicting freeze drying characteristics of mashed nteat, especially for the influence of sublimation temperature and thermal conductivity.